Effects of Dietary Energy Level and Tanniferous Acacia karroo Leaf Meal Level of Supplementation at Finisher Stage on Performance and Carcass Characteristics of Ross 308 Broiler Chickens in South Africa - Ngambi, J.W.; Nakalebe, P.M.; Norris, D.; Malatje, M.S.; Mbajiorgu, C.A. (International Journal of Poultry Science, 2008)
The study was conducted to determine the effect of dietary energy level and tanniniferous Acacia karroo leaf meal level of supplementation at finisher stage on performance and carcass characteristics of male and female Ross 308 broiler chickens. Three hundred and sixty, 21 days old male and female broiler chickens were assigned to twelve treatments with three replications of ten birds in a 2 (sex) x 3 (dietary energy level) x 3 (tanniniferous Acacia karroo leaf meal level) factorial, complete randomized design. Supplementation with Acacia karroo leaf meal had no effect on diet intake, digestibility and live weight of broiler chickens. However, supplementation with 9 and 12 g of Acacia karroo leaf meal per kg DM feed reduced fat pad weights in male broiler chickens by 26 and 29% points, respectively. Similarly, supplementation with 9 and 12 g of Acacia karroo leaf meal per kg DM feed reduced fat pad weights in female chickens by 26% points. These reductions were achieved without any significant reduction in feed intake and digestibility. However, the physiological explanation for this effect is not clear and it, thus, merits further investigation.